THE INFLUENCE OF EASE OF USE, E-SERVICE QUALITY AND PERCEIVED USEFULNESS AS AN INTERVENING VARIABLE AN INTENTION TO REUSE ZALORA ONLINE FASHION APPLICATION - Pratiwi, Delya; Rahmiati, Rahmiati; Abror, Abror (STIE Ekuitas, 2022)
This study aims to analyze (1) the effect of ease of use on perceived usefulness on Zalora users. (2) The effect of e-service quality on perceived usefulness on Zalora users. (3) The effect of ease of use on intention to reuse on Zalora users. (4) The effect of e-service quality on intention to reuse of Zalora users. (5) The effect of perceived usefulness on intention to reuse on Zalora users. The population on this study is Zalora users who had shopped more than once. The total sample of this research was 224 people by using online questionnaire. Data processing was carried out through SmartPLS software. The result of research show that (1) Ease of use has a negative and insignificant effect on perceived usefulness on Zalora users. (2) E-service quality has a positive and significant effect on perceived usefulness on Zalora users. (3) Ease of use has a positive and significant effect on intention to reuse on Zalora users. (4) E-service quality has a positive and significant effect on intention to reuse on Zalora users. (5) Perceived usefulness has a positive and significant effect on intention to reuse on Zalora users. For the future study it is better to explore more about variable that can influence intention to reuse.